Blood transfusion is associated with impaired outcome after transcatheter aortic valve implantation. Issue 3 (24th October 2014) - Seiffert, Moritz; Conradi, Lenard; Terstesse, Ann Christine; Koschyk, Dietmar; Schirmer, Johannes; Schnabel, Renate B.; Wilde, Sandra; Ojeda, Francisco M.; Reichenspurner, Hermann; Blankenberg, Stefan; Schäfer, Ulrich; Treede, Hendrik; et al.
<x xml:space="preserve">Abstract</x> Objectives We sought to evaluate the relationship of blood transfusion after transcatheter aortic valve implantation (TAVI) and mid‐term outcome to improve patient selection and periprocedural treatment. Background Increasing evidence suggests a negative influence of blood transfusion on outcomes of patients with cardiovascular diseases. While the adverse impact of bleeding events on survival has been documented after TAVI, data on the impact of postoperative blood transfusions are scarce. Methods TAVI was performed in 700 consecutive patients; 14.7% of TAVI patients suffered from bleeding or access site complications and were excluded from analysis to minimize confounding. Outcomes were analyzed with emphasis on blood transfusions and according to the Valve Academic Research Consortium definitions. Median follow‐up duration was 364 days. Multivariable analyses were performed to identify predictors for transfusion and 1‐year mortality. Results 33.0% of patients received blood transfusions after TAVI, irrespective of access choice. Blood transfusions were associated with a higher baseline risk profile (median logistic EuroSCORE 21.0 vs. 17.0%), increased rates of postoperative complications and impaired survival (21.2 vs. 36.1% all‐cause 1‐year mortality). Transfusion was an independent predictor of mortality at 1 year (OR 2.78 [CI 1.59–4.86]). Low body mass index (OR 0.94 [0.89–1.0]), low baseline hemoglobin (OR 0.39 [0.33–0.47]) and combined anticoagulation/antiplatelet therapy were identified as independent predictors of blood transfusion after TAVI. Conclusions Blood transfusions were frequently required after TAVI even in the absence of overt bleeding or access site complications and were identified as an independent predictor of impaired mid‐term outcome. Optimization of baseline factors, strict blood conservation strategies, and individualized antiplatelet or anticoagulant regimens may improve outcome after TAVI. © 2014 Wiley Periodicals, Inc.